Building High Power Density of Sodium-Ion Batteries: Importance of Multidimensional Diffusion Pathways in Cathode Materials - Chen, Mingzhe; Zhang, Yanyan; Xing, Guichuan; Tang, Yuxin (Frontiers in Chemistry, 2020)
Emerging sodium-ion batteries (SIBs) devices hold the promise to leapfrog over existing lithium-ion batteries technologies with respect to desirable power/energy densities and the abundant sodium sources on the earth. To this end, the discoveries on novel cathode materials with outstanding rate capabilities are being given high priority in the quest to achieve high power density SIBs devices, and the multi-dimensional Na+ migration pathways with low diffusion energy barriers are crucial. In light of this, the recent development of Prussian blue analogs and sodium superionic conductor (NASICON)-type materials with 3D Na+ diffusion pathways for building high power density NIBs are provided in this perspective. Ultimately, the future research directions to realize them for real applications are also discussed.